Adult and endemic neurogenesis in the vestibular nuclei after unilateral vestibular neurectomy. (January 2021) - Rastoldo, Guillaume; El Mahmoudi, Nada; Marouane, Emna; Pericat, David; Watabe, Isabelle; Toneto, Alain; López-Juárez, Alejandra; Chabbert, Christian; Tighilet, Brahim
Highlights: Vestibular neurectomy (UVN) induces adult neurogenesis in the deafferented MVN. First demonstration of adult oligodendrogenesis in the deafferented MVN after UVN. First demonstration of neural stem cells activation in the deafferented MVN. Potential adult neurogenic niche status for the vestibular nuclei. Abstract: We previously revealed adult reactive neurogenesis in deafferented vestibular nuclei following unilateral vestibular neurectomy (UVN) in the feline model. We recently replicated the same surgery in a rodent model and aimed to elucidate the origin and fate of newly generated cells following UVN. We used specific markers of cell proliferation, glial reaction, and cell differentiation in the medial vestibular nucleus (MVN) of adult rats. UVN induced an intense cell proliferation and glial reaction with an increase of GFAP-Immunoreactive (Ir), IBA1-Ir and Olig2-Ir cells 3 days after the lesion in the deafferented MVN. Most of the newly generated cells survived after UVN and differentiated into oligodendrocytes, astrocytes, microglial cells and GABAergic neurons. Interestingly, UVN induced a significant increase in a population of cells colocalizing SOX2 and GFAP 3 days after lesion in the deafferented MVN indicating the probable presence of multipotent cells in the vestibular nuclei. The concomitant increase in BrdU- and SOX2-Ir cells with the presence of SOX2 and GFAP colocalization 3 days after UVN in the deafferented MVN may support local mitotic activity of endemic quiescent neural stem cells in the parenchyma of vestibular nuclei.